Social Status of Transgender Individuals in the Prophetic Era and in Modern Pakistan - Bano, Shehar (El Nubuwwah Jurnal Studi Hadis, 2024)
The research study investigates how transgender people were treated in both the time of Prophet Muhammad and contemporary Pakistan which has led to major transformations in social responses and legal systems and religious doctrinal perspectives. Linking to research findings shows early Islamic society recognized and respected mukhannathun transgender people but modern Pakistan includes legal progress alongside continued social discrimination against transgender groups. The analysis of transgender rights reveals how religious beliefs interact with cultural heritage as well as modern lawmaking regarding transgender people's rights protection. Islamic principles of justice and compassion form the basis of inclusivity but social prejudices alongside historical changes have led to marginalization. Through the Transgender Persons (Protection of Rights) Act, 2018 Pakistan has achieved legal recognition but social acceptance and legal recognition exist in significant tension with one another. This study entails multiple constraints which affect its effectiveness. The study of the Prophetic era depends mostly on scarce textual evidence which receives varied interpretations through different Islamic scholarly positions. The contemporary issues which transgender individuals in Pakistan experience are changing and need further research for understanding how legal changes specifically affect their everyday life. The research adds value to present transgender rights scholarship through its analysis of Islamic perspectives at different historical periods. The study performs a comprehensive analysis of transgender rights interactions between Prophet Muhammad's time and present-day Pakistan through documented comparative examinations. Future scholarly attention should adapt towards examining how Pakistani transgender rights can become practical while exploring religious scholar involvement and government decision making in creating inclusive Pakistan. Research that examines transgender rights approaches inside Muslim-majority nations will give important insights regarding Islamic perspectives on transgender matters.